Analisis perbandingan rencana strategi pada BMT X, BMT Y, dan BMT Z dalam mengembangkan ekonomi bangsa - Prasetyo Utomo, Mahesa Dwi; Arifiandi, Muhammad Arfan; Zakhrafi, Muhammad Zahid (Maliki Interdisciplinary Journal, 2024)
This article discusses the role and marketing strategies of Baitul Maal wat Tamwil (BMT) in the development of Islamic economy in Indonesia. BMT is a microfinance institution that operates as a cooperative and focuses on the micro and small-medium enterprises (MSMEs) sector. BMT combines the concepts of Baitul tamwil (wealth development house) and Baitul maal (wealth house) to promote productive businesses, savings, and economic activities. BMT manages funds by collecting and investing them, and distributes profits to those in need. BMT plays a crucial role in the development of Islamic economy in Indonesia and aims to empower communities and reduce poverty and unemployment. BMT has different visions, missions, and strategic plans, but all of them focus on providing the best financial services and promoting Islamic values. They use various marketing strategies such as segmentation, targeting, positioning, and differentiation to attract customers and promote their products.